Udmurt Animist Ceremonies in Bashkortostan: Fieldwork Ethnography - Eva Toulouze; Liivo Niglas (Journal of Ethnology and Folkloristics)
Ethnography of religious ceremonies by the Bashkortostan Udmurt. A short introduction based on fieldwork.